Synthesis and charaterization of polyamide (PA) forward osmosis membrane - Hie Lian, Hii (2015)
This paper presents the synthesis and characterization of polyamide forward osmosis membrane. Forward osmosis (FO) is a process where the osmotic pressure difference occurs between two different concentration solutions is equalized by the transport of water through the semi permeable membrane from less concentrated region to a higher concentrated region. Forward osmosis can be used to solve the problem of yellowish water that is delivered to consumer. In this study, polyamide forward osmosis membrane was produced through interfacial polymerization by using m-phenylenediamene (2% wt) and trimesosyl chloride (0.15% wt) as active monomer. Humic acid was used as the feed solution and NaCl (0.5M, 1.0M, 1.5M, 2.0M and 2.5 M) as the draw solution. The weight of the humic acid was recorded for every 10 minutes to calculate it water flux. Humic acid and draw solution were measured using conductivity and UV-Vis to record it conductivity and absorption value. When the concentration of draw solution is 0.5 M, the water flux is 1.030×10-4 m3/ m2min while when the draw solution concentration is 2.5 M the water flux is 1.390×10-4 m3/ m2min.Humic acid rejection is 97.1 which were highest when the draw solution is 2.5M. When concentration of draw solution increases the water flux also increase. This increase is contributed by the increasing osmotic pressure. FO can be used in wastewater treatment, control drug release and food processing.